The pathway intermediate 2‐keto‐3‐deoxy‐L‐galactonate mediates the induction of genes involved in D‐galacturonic acid utilization in Aspergillus niger - Alazi, Ebru (John Wiley and Sons Inc., 2017)

(untitled) (FEBS Lett)
In Aspergillus niger, the enzymes encoded by gaaA, gaaB, and gaaC catabolize d‐galacturonic acid (GA) consecutively into l‐galactonate, 2‐keto‐3‐deoxy‐l‐galactonate, pyruvate, and l‐glyceraldehyde, while GaaD converts l‐glyceraldehyde to glycerol. Deletion of gaaB or gaaC results in severely impaired growth on GA and accumulation of l‐galactonate and 2‐keto‐3‐deoxy‐l‐galactonate, respectively. Expression levels of GA‐responsive genes are specifically elevated in the ∆gaaC mutant on GA as compared to the reference strain and other GA catabolic pathway deletion mutants. This indicates that 2‐keto‐3‐deoxy‐l‐galactonate is the inducer of genes required for GA utilization.